2009
DOI: 10.1016/j.talanta.2009.07.060
|View full text |Cite
|
Sign up to set email alerts
|

Six orders of magnitude dynamic range in capillary electrophoresis with ultrasensitive laser-induced fluorescence detection

Abstract: An ultrasensitive laser-induced fluorescence detector was used with capillary electrophoresis for the study of 5-carboxy-tetramethylrhodamine. The raw signal from the detector provided roughly three orders of magnitude dynamic range. The signal saturated at high analyte concentrations due to the dead time associated with the single-photon counting avalanche photodiode employed in the detector. The signal can be corrected for the detector dead time, providing an additional order of magnitude dynamic range. To f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…1214 To address this very wide variation in uptake and metabolic activity, we have created a set of fluorescence detectors with six to nine orders of magnitude dynamic range. 1516 These instruments have revealed that cultured PC12 cells tend to generate very similar expression profiles of fluorescent glycolipids, which provides confidence in the reproducibility of the analytical method. In constrast, neurons provide a quite diverse population of metabolic products, undoubtedly reflecting differences in their function.…”
mentioning
confidence: 98%
“…1214 To address this very wide variation in uptake and metabolic activity, we have created a set of fluorescence detectors with six to nine orders of magnitude dynamic range. 1516 These instruments have revealed that cultured PC12 cells tend to generate very similar expression profiles of fluorescent glycolipids, which provides confidence in the reproducibility of the analytical method. In constrast, neurons provide a quite diverse population of metabolic products, undoubtedly reflecting differences in their function.…”
mentioning
confidence: 98%
“…Briefly, fluorescence was excited using a CW 532 nm diode-pumped laser (CrystaLaser Model CL532-025), which was focused into the sample stream at the center of a sheath-flow cuvette. Fluorescence was collected at right angles and detected by a cascade of single-photon counting avalanche photodiode modules (PerkinElmer, Montreal, PQ Canada) with a sampling frequency of 50 Hz [23,24]. …”
Section: Methodsmentioning
confidence: 99%
“…Our laser-induced fluorescence instrument has been described in detail elsewhere [3441]. Briefly, a multipurpose injection block was connected to a CZE1000R high-voltage power supply (Spellman).…”
Section: Methodsmentioning
confidence: 99%
“…The data was processed using SigMan 1.2.6 (http://sourceforge.net/projects/sigman/), and plotted in Matlab (Mathworks). The data were corrected for photodetector nonlinearity before further processing [4041]. The corrected data were treated with a 5-point median filter to remove spikes caused by the passage of particles through the laser beam and then smoothed by convolution with a Gaussian function that had a 5-point (0.5 s) standard deviation.…”
Section: Methodsmentioning
confidence: 99%